Constructing "British Values" within a Radicalisation Narrative: The reporting of the Trojan Horse affair. (17th February 2018) - Poole, Elizabeth
Abstract : This article examines the reporting of the "Operation Trojan Horse" affair in two British newspapers, the Daily Mail and The Guardian, in 2014. I argue that this high-profile case was a vehicle for the Conservative-led Government, and parts of the United Kingdom's press, to advance their doctrine of muscular liberalism, an ideology that locates the rise of extremism in the policies of multiculturalism. In this interpretation of the event, it was argued that, under a Labour council, schools in Birmingham had been given the freedom to practise a segregationist agenda, resulting in an infiltration of Islamist ideology. Through a radicalisation narrative, that locates the causes of terrorism with extremist thought, an issue of local governance and agency was transformed into an argument about terrorist radicalisation. This allowed Government agencies to intervene, at a local and national level, promoting an assimilationist agenda through conceptualisations of national identity, here constructed as "British values".